Activated Fly Ash Blended Cement - MAGUDESWARAN, P.N.; MALATHI, M.; GEORGE, SUNILAA (Asian Journal of Chemistry, 2010)
Developing and under developing countries increases the annual cement production exponentially, since it relates the growth and economy of the country. The production of one Tonne of cement contributes about 1.1 Tonne of carbon dioxide gas to the atmosphere together with oxides of nitrogen and methane. These are the main pollutants of the atmosphere which leads to the global warming. The total carbon dioxide contribution by the world cement production industries accounts around 7%. This paper discusses the issues of global warming and the need for the development of efficient blending material of concrete. Activated fly ash concrete at various replacement levels was found that it reduces the emission of CO2 gases and enhances the inhibition to corrosive atmosphere.